We Pursue Our Magic: A Spiritual History of Black Feminism - Magloire, Marina (University of North Carolina Press, 2023)
"In this book, Marina Magloire draws on the collected archives of distinguished 20th century Black woman artists and writers such as Lucille Clifton, Katherine Dunham, Audre Lorde, Toni Cade Bambara, Lorraine Hansberry, Nina Simone, and Zora Neale Hurston to trace a new history of Black feminist thought in relation to Afro-diaspora religion. She offers an alternative genealogy of Black feminism beginning in the 1930s with the path breaking ethnographic work of Katherine Dunham and Zora Neale Hurston in Haiti and ending with the present-day popularity of Afro-diasporic spiritual practices among Black women"--